2014
DOI: 10.1159/000368344
|View full text |Cite
|
Sign up to set email alerts
|

Capsule Contraction Syndrome with a Microincision Foldable Hydrophilic Acrylic Intraocular Lens: Two Case Reports and Review of the Literature

Abstract: Here we present 2 cases of capsule contraction syndrome (CCS). In both cases, a hydrophilic acrylic Akreos MI60 (Bausch and Lomb) intraocular lens (IOL) was implanted in the capsular bag through microincision cataract surgery, and the literature on the subject is reviewed. Since CCS has been described after the implantation of every IOL type, it is unlikely that the Akreos MI60 chemical and physical properties may cause CCS. When CCS occurs with IOLs composed of increasingly flexible materials that are inserte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Mydriatic examination should be conducted when patients complain of vision or visual change in order to detect CCS early and provide timely treatment. Laser and surgery are the primary treatments for CCS (25,26). However, in some severe cases or cases not suitable for laser treatment, surgery is the sole choice.…”
Section: Discussionmentioning
confidence: 99%
“…Mydriatic examination should be conducted when patients complain of vision or visual change in order to detect CCS early and provide timely treatment. Laser and surgery are the primary treatments for CCS (25,26). However, in some severe cases or cases not suitable for laser treatment, surgery is the sole choice.…”
Section: Discussionmentioning
confidence: 99%
“…The thickness of PCL is usually constant and corresponds to the length of the cilia (3-10μm) [25][26]. Both layers are continuously transported by the synchronized rhythmic beating of cilia (the mucociliary transport -MCT) at a speed of about 3 mm/min towards the pharynx [1,17,26].…”
Section: Airways Surface Liquidmentioning
confidence: 99%
“…The airway epithelium is covered with a thin, liquid protective layer -Airways Surface Liquid (ASL) [1]. ASL is created and maintained by water and ion transport, especially sodium and chloride [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anterior capsule opacity(ACO) and shrinkage may decrease visual function [ 2 ]. The development of CCS can lead to IOL decentration [ 3 ], IOL dislocation [ 4 ], and even ciliary body detachment [ 5 ]. Previous studies showed that CCS was more prevalent among patients with some preexisting ocular or systemic disorders, such as high myopia [ 6 ], retinitis pigmentosa [ 7 ] and diabetes mellitus [ 8 ].…”
Section: Introductionmentioning
confidence: 99%